2021
DOI: 10.5937/fme2102367s
|View full text |Cite
|
Sign up to set email alerts
|

Study of geometric characteristics of the arc teeth semi-rolled cylindrical gear meshing

Abstract: In the conditions of unbraced machine body parts, arc teeth cylindrical gears have a higher load capacity, durability and reliability as well as the ability to compensate for the twist angle by self-adjustment of one of the wheels compared to straight and helical teeth gears. Use of such gears in a semi-rolled version allows simplifying significantly the technological process of cutting wheels and making gears with large gear ratios. In this article, mathematical models of wheel and gear arc teeth forming proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
1
0
6
Order By: Relevance
“…They also created an algorithm and program for computing the coordinates of the arc tooth meshing active line. The results indicated that in the case of errors in the relative positions of gears and hubs, the geometric characteristics of arc tooth meshing could help calculate its load-bearing capacity and durability [10].…”
Section: Related Workmentioning
confidence: 99%
“…They also created an algorithm and program for computing the coordinates of the arc tooth meshing active line. The results indicated that in the case of errors in the relative positions of gears and hubs, the geometric characteristics of arc tooth meshing could help calculate its load-bearing capacity and durability [10].…”
Section: Related Workmentioning
confidence: 99%
“…Поверхность прямого кругового конуса образуется вращением прямолинейной режущей кромки резца, расположенной в плоскости, проходящей через ось резцовой головки, вокруг этой оси. Проекции радиус-вектора производящей поверхности резцовой головки имеют вид [3]:…”
Section: математические модели процесса формообразования главных пове...unclassified
“…-угол наклона режущей кромки относительно оси (угол исходного производящего контура); -расчетный радиус резцовой головки при нарезании колеса. Проекции орта нормали поверхности (1) описываются выражениями [3]:…”
Section: математические модели процесса формообразования главных пове...unclassified
See 2 more Smart Citations